2015
DOI: 10.1103/physrevb.92.085119
|View full text |Cite
|
Sign up to set email alerts
|

Testing predictions from density functional theory at finite temperatures:β2-like ground states in Co-Pt

Abstract: We perform a critical assessment of the accuracy of DFT-based methods in predicting stable phases within the Co-Pt binary alloy. Statistical mechanical analysis applied to zero kelvin DFT predictions yields finite-temperature results that can be directly compared with experimental measurements. The predicted temperature-composition phase diagram is qualitatively incompatible with experimental observations, indicating that the predicted stability of long-period superstructures as ground states in the Co-Pt bina… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 92 publications
(111 reference statements)
1
10
0
Order By: Relevance
“…Similar problems with the magnitudes of formation energies and the β 2 structure stability has recently been reported also for the Co-Pt system [7] and the authors of that paper speculate that related alloys, such as Fe-Pt, Ni-Pt, Fe-Ni, are likely to be plagued by the same or similar issues. Recently, Zhang et al have shown that nonlocal hybrid functionals, such as the Heyd-Scuseria-Ernzerhof (HSE06, but hereafter just HSE) [15,16], can effectively fix both the formation energy and the phase stability problems in Cu-Au.…”
Section: From Experimental Point Of View This Is a Conflict Becausesupporting
confidence: 76%
See 2 more Smart Citations
“…Similar problems with the magnitudes of formation energies and the β 2 structure stability has recently been reported also for the Co-Pt system [7] and the authors of that paper speculate that related alloys, such as Fe-Pt, Ni-Pt, Fe-Ni, are likely to be plagued by the same or similar issues. Recently, Zhang et al have shown that nonlocal hybrid functionals, such as the Heyd-Scuseria-Ernzerhof (HSE06, but hereafter just HSE) [15,16], can effectively fix both the formation energy and the phase stability problems in Cu-Au.…”
Section: From Experimental Point Of View This Is a Conflict Becausesupporting
confidence: 76%
“…We also notice that HSE and PBE0 predict almost identical formation energies, which could indicate that Cu-Au is not very sensitive to the screening length details of the HSE functional. For example, Co-Pt has been reported to be a problematic system for HSE due to the unsuitability of the standard HSE screening length for Co [7]. The above findings suggest that one-iteration hybrids can be a viable alternative to the much slower fully self-consistent hybrid calculations, at least for the properties and the type of systems considered here.…”
Section: Formation Energiesmentioning
confidence: 85%
See 1 more Smart Citation
“…Difficulties with DFT calculations were shown in the past for complexes containing two interacting transition metals. 9 Mononuclear metal centres are much simpler. Furthermore, calculations using B3LYP were approximately two-fold faster than by using PW91 and PBE0 and showed only slight differences in energies between 0.016% and 0.042% ( Fig.…”
mentioning
confidence: 99%
“…In this way, complex energy landscapes as a function of configurational degrees of freedom can be reproduced by fitting to a relatively small number of first-principles electronic structure calculations. The approach has enabled accurate first-principles predictions of temperature-composition phase diagrams, [23][24][25][26][27][28][29][30][31][32][33][34] order-disorder phenomena, [35][36][37][38][39][40][41][42][43][44][45] and composition-dependent diffusion coefficients in alloys and complex inorganic compounds. [46][47][48][49][50][51][52] A cluster expansion is formulated as a linear series of cluster basis functions multiplied by constant expansion coefficients that are determined by the underlying chemistry and crystal structure of the multicomponent solid.…”
Section: Introductionmentioning
confidence: 99%